Vibration Faults Simulation System (VFSS): A System for teaching and training on fault detection and diagnosis - Abdul Muthalif, Asan Gani; Salami, Momoh Jimoh Eyiomika (2002)
Machine condition monitoring is vital in many plants as any shutdown can lead to both materials and financial losses. Since vibration fault signals and their causes are important for fault detection and diagnosis, a Vibration Faults Simulation System (VFSS) is developed to gain good understanding of vibration faults signals. This paper is aimed at simulating and analyzing vibration fault signals, which can be useful for teaching and training purposes especially for .companies dealing with predictive maintenance. To achieve this a Vibration Faults Simulation Rig (VFSR) is designed and developed to simulate and study most common vibration faults signals encountered in rotating machines. A LabVIEW-based Data Acquisition System (DAS) is used to process the fault signals. The complete system was developed and tested and the fault signals were compared with normal signals so as to ascertain the condition of the machine under investigation